A novel highly sensitive dual-channel chemical sensor for sequential recognition of Cu2+ and CN− in aqueous media and its bioimaging applications in living cells. (22nd September 2021) - Xie, Yong-Qiang; Zhang, You-Ming; Li, Zhao-Hui; Qi, Xiao-Ni; Yao, Hong; Shi, Bing-Bing; Qu, Wen-Juan; Wei, Tai-Bao; Lin, Qi
Abstract : A simple and unique dual-channel chemical probe (DH) was designed and synthesized, which not only realized sequential recognition of Cu 2+ and CN − by colorimetric and fluorometric methods, but also realized fluorescence detection of CN − . Abstract : A simple and unique dual-channel chemical probe (DH) was designed and synthesized, which not only realized sequential recognition of Cu 2+ and CN − by colorimetric and fluorometric methods, but also realized fluorescence detection of CN − . When different cations (Co 2+, Mg 2+, Ni 2+, Cd 2+, Hg 2+, Al 3+, Ag +, Cu 2+, Pb 2+, Fe 3+, Zn 2+ and Ca 2+ ) were added into the solution containing the probe molecule DH, only Cu 2+ induced an observable change in the UV-vis and fluorescence spectra, indicating that the probe molecule can be applied for specific recognition of Cu 2+ . The anti-interference experiment of DH to Cu 2+ showed that DH has good selectivity for detecting Cu 2+, with a detection limit of 7.05 × 10 −7 M. In particular, the fluorescence "ON–OFF–ON" process can be recycled by sequentially adding Cu 2+ and EDTA, and the fluorescence intensity remained unchanged after ten times. This observation suggested that DH can achieve reversible highly sensitive response to Cu 2+ and EDTA, and can be used as a hypersensitive logic gate for Cu 2+ detection. More interestingly, when different anions (CH3 COO −, SO3 2−, H2 PO4 −, ClO4 −, NO3 −, HSO4 −, I −, Cl −, F −, Br −, N3 − and CN − ) were added into the solution containing DH and Cu 2+, only CN − induced color change of the solution from red to yellowish green, and the fluorescence intensity greatly enhanced, indicating that DH-Cu 2+ has a specific response to CN − . The anti-interference experiment showed that DH-Cu 2+ has good selectivity for CN −, with a detection limit of 8.11 × 10 −6 M. Moreover, the probe molecule DH can detect CN −, with a detection limit of 7.61 × 10 −6 M. Experimental and theoretical methods were applied to deeply study the detection mechanism of DH, present great potential in practical application for ion test strips and HeLa cell imaging reagents.